Propagation of hippocampal ripples to the neocortex by way of a subiculum-retrosplenial pathway - Noam Nitzan (Nature Portfolio, 2020)
Communication between the hippocampus and neocortex is organized through high frequency sharp wave ripple activity. Here, the authors report ripple activity coupling between the hippocampus and granular retrosplenial cortex suggesting an involvement in communicating with the neocortex.